2014
DOI: 10.1021/np500396y
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Natural and Non-natural Curcuminoids and Their Neuroprotective Activity against Glutamate-Induced Oxidative Stress in HT-22 Cells

Abstract: A strategy for the synthesis of natural and non-natural 5-deoxy-6,7-dihydrocurcuminoids (diarylheptanoids) was developed for the preparation of 14 compounds with varying aromatic substituent patterns and a different functionality in the aliphatic seven-carbon chain. The in vitro protective activity against glutamate-induced neuronal cell death was examined in the murine hippocampal cell line HT-22 to find structural motifs responsible for neuroprotective effects in vitro. Among the tested compounds the ferulic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 48 publications
0
28
0
Order By: Relevance
“…The NMR data are identical to those of reported trans-coniferyl aldehyde. [5] Compound 3 was isolated as a white solid, mp 280- . Analytical NMR and MS data indicated that the structure of 4 is stigmastane 3β,5α,6β-triol.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The NMR data are identical to those of reported trans-coniferyl aldehyde. [5] Compound 3 was isolated as a white solid, mp 280- . Analytical NMR and MS data indicated that the structure of 4 is stigmastane 3β,5α,6β-triol.…”
Section: Resultsmentioning
confidence: 99%
“…A phytochemical study of the ethyl acetate extract of the stems of M. balansae led to the isolation of six compounds including (-)-dehydroxycubebin (1), trans-coniferyl aldehyde (2), 3,3',4'-tri-O-methyl ellagic acid (3), stigmastane 3β,5α,6β-triol (4), 2,3dihydroxy-1-(4'-hydroxy-3'-methoxyphenyl) propan-1-one (5), and protocatechuic acid (6). Their chemical structures were elucidated by spectroscopic NMR and MS data.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, 1,7‐bis‐(3,4‐dihydroxyphenyl)hept‐4‐ene‐3‐one ( i4 ) and 1,7‐bis(4‐hydroxyphenyl)‐hept‐4‐ene‐3‐one ( i11 ) were also identified in methanolic extracts from the barks of birch and alder species ,,,. Moreover, 1,7‐bis(4‐hydroxyphenyl)‐3‐hydroxyhept‐3‐ene ( i10 ) was described in the literature as well . Compounds i9 , i12 , i13 , i14 , i15 , and i16 could not be assigned to an exact chemical structure yet because various isomeric structures are present in these examples.…”
Section: Resultsmentioning
confidence: 99%
“…[12,14c,17,19] Moreover, 1,7-bis(4-hydroxyphenyl)-3hydroxyhept-3-ene (i10) was described in the literature as well. [18] Compounds i9, i12, i13, i14, i15, and i16 could not be assigned to an exact chemical structure yet because various isomeric structures are present in these examples.…”
Section: Idmentioning
confidence: 98%